A self-supported 3D aerogel network lithium–sulfur battery cathode: sulfur spheres wrapped with phosphorus doped graphene and bridged with carbon nanofibers. Issue 16 (14th April 2020) - Tan, Junchao; Li, Dan; Liu, Yuqing; Zhang, Peng; Qu, Zehua; Yan, Yan; Hu, Hao; Cheng, Haoyan; Zhang, Jiaoxia; Dong, Mengyao; Wang, Chao; Fan, Jincheng; et al.
Abstract : An integrated PGCNF/S aerogel with a "network" structure has effectively restricted the shuttling of polysulfides and exhibited promising lithium ion storage capability. Abstract : Practical applications of lithium–sulfur batteries have been impeded by their poor cycling stability that results from the "shuttling" of polysulfides. Herein, we demonstrate a new strategy for developing a hierarchical phosphorus-doped graphene/carbon nanofiber/sulfur aerogel (PGCNF/S) with "network" morphologies, in which sulfur spheres are wrapped with graphene sheets and carbon nanofibers (PGCNFs) with "net" structures and this carbon matrix has greatly improved the electrochemical performances of sulfur spheres. PGCNF nets ensure a uniform loading of sulfur spheres that leads to a high sulfur mass loading of 85 wt%. Also, the good porous structures achieved with this PGCNF/S cathode can provide sufficient space for volume expansion of active sulfur spheres. Due to its structural advantages, this binder-free PGCNF/S cathode exhibits a specific capacity of 1360 mA h g −1 at 0.1C, and a high areal capacity of 21.5 mA h cm −2 based on a high sulfur mass loading of 15.8 mg cm −2 . Furthermore, a long term cycling stability of 600 cycles has been achieved by this PGCNF/S cathode with an average coulombic efficiency of ∼99.8%. This work highlights a broadly adaptable strategy of "network" structures for developing scalable and high-energy density electrode materials for energy storage devices.